Sensory profile, ferritin and zinc levels in preschool-aged children with symptoms of attention deficit hyperactivity disorder - Yoldaş, Tuba Çelen; Huri, Meral; Kayıhan, Hülya; Karakaya, Jale; Özmert, Elif N. (The Turkish Journal of Pediatrics, 2020)
Background. Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders and has a big impact on the well-being of children. The disorder can lead to noticeable functional limitations for children and bio-ecological factors also contribute to symptoms of ADHD. We aimed to investigate the associations between ADHD symptoms and some related bio-ecological factors including serum ferritin, zinc levels and sensory processing in preschool-aged children. Methods. Twenty-two children who had been referred to the division of Developmental Pediatrics because of ADHD symptoms and 22 participants from the general pediatric outpatient clinics were included in the study. The symptoms of ADHD were evaluated with Conners` Parent Rating Scale-Revised Short form. Complete blood count, serum ferritin and zinc levels were also evaluated. A blind occupational therapist implemented sensory processing measurements. The characteristics of each participant such as prematurity, perinatal complications, developmental practices and sociodemographic data were also considered. Results. Sensory processing measurement analysis revealed that all Sensory Profile scores were significantly lower in the children with ADHD symptoms compared to the control group indicating that the child shows the behavior more than desired. The low level of zinc (p=0.026, OR=6.153, 95% CI= 1.247-30.362) and the presence of perinatal complications (p=0.045, OR=10.864, 95% CI=1.059-111.499) increased the risk of ADHD symptoms. We could not find an association for ferritin levels in our study. Conclusions. The evaluation of zinc level and sensory profile parallel to other strategies can be recommended during the management of ADHD symptoms in preschool children.
Keywords: attention deficit hyperactivity disorder; ferritin; sensory profile; zinc